A comparison of four methods of tonometry: method agreement and interobserver variability. Issue 7 (17th June 2005) - Tonnu, P-A; Ho, T; Sharma, K; White, E; Bunce, C; Garway-Heath, D
Abstract : Aim: To compare the inter-method agreement in intraocular pressure (IOP) measurements made with four different tonometric methods. Methods: IOP was measured with the Goldmann applanation tonometer (GAT), Tono-Pen XL, ocular blood flow tonograph (OBF), and Canon TX-10 non-contact tonometer (NCT) in a randomised order in one eye of each of 105 patients with ocular hypertension or glaucoma. Three measurements were made with each method, and by each of two independent GAT observers. GAT interobserver and tonometer inter-method agreement was assessed by the Bland-Altman method. The outcome measures were 95% limits of agreement for IOP measurements between GAT observers and between tonometric methods, and 95% confidence intervals for intra-session repeated measurements. Results: The mean differences (bias) in IOP measurements were 0.4 mm Hg between GAT observers, and 0.6 mm Hg, 0.1 mm Hg, and 0.7 mm Hg between GAT and Tono-Pen, OBF, and NCT, respectively. The 95% limits of agreement were smallest (bias ±2.6 mm Hg) between GAT observers, and larger for agreement between the GAT and the Tono-Pen, OBF, and NCT (bias ±6.7, ±5.5, and ±4.8 mm Hg, respectively). The OBF and NCT significantly underestimated GAT measurements at lower IOP and overestimated these at higher IOP. The repeatability coefficients for intra-session repeated measurement for each method were ±2.2 mm Hg and ±2.5 mm Hg for the GAT, ±4.3 mm Hg for the Tono-Pen, ±3.7 mm Hg for the OBF, and ±3.2 mm Hg for the NCT. Conclusions: There was good interobserver agreement with the GAT and moderate agreement between the NCT and GAT. The differences between the GAT and OBF and between the GAT and Tono-Pen probably preclude the OBF and Tono-Pen from routine clinical use as objective methods to measure IOP in normal adult eyes.